Spectrally selective three‐dimensional dynamic balanced steady‐state free precession for hyperpolarized C‐13 metabolic imaging with spectrally selective radiofrequency pulses. Issue 3 (21st October 2016) - Shang, Hong; Sukumar, Subramaniam; von Morze, Cornelius; Bok, Robert A.; Marco‐Rius, Irene; Kerr, Adam; Reed, Galen D.; Milshteyn, Eugene; Ohliger, Michael A.; Kurhanewicz, John; Larson, Peder E.Z.; Pauly, John M.; et al.
Abstract : Purpose: Balanced steady‐state free precession (bSSFP) sequences can provide superior signal‐to‐noise ratio efficiency for hyperpolarized (HP) carbon‐13 ( 13 C) magnetic resonance imaging by efficiently utilizing the nonrecoverable magnetization, but managing their spectral response is challenging in the context of metabolic imaging. A new spectrally selective bSSFP sequence was developed for fast imaging of multiple HP 13 C metabolites with high spatiotemporal resolution. Theory and Methods: This novel approach for bSSFP spectral selectivity incorporates optimized short‐duration spectrally selective radiofrequency pulses within a bSSFP pulse train and a carefully chosen repetition time to avoid banding artifacts. Results: The sequence enabled subsecond 3D dynamic spectrally selective imaging of 13 C metabolites of copolarized [1‐ 13 C]pyruvate and [ 13 C]urea at 2‐mm isotropic resolution, with excellent spectral selectivity (∼100:1). The sequence was successfully tested in phantom studies and in vivo studies with normal mice. Conclusion: This sequence is expected to benefit applications requiring dynamic volumetric imaging of metabolically active 13 C compounds at high spatiotemporal resolution, including preclinical studies at high field and, potentially, clinical studies. Magn Reson Med 78:963–975, 2017. © 2016 International Society for Magnetic Resonance in Medicine.